2020
DOI: 10.1084/jem.20192291
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cell reactivation by diverse antigen-presenting cells imparts distinct functional responses

Abstract: CD8+ tissue-resident memory T cells (TRM cells) are poised at the portals of infection and provide long-term protective immunity. Despite their critical roles, the precise mechanics governing TRM cell reactivation in situ are unknown. Using a TCR-transgenic Nur77-GFP reporter to distinguish “antigen-specific” from “bystander” reactivation, we demonstrate that lung CD8+ TRM cells are reactivated more quickly, yet less efficiently, than their counterparts in the draining LNs (TLN cells). Global profiling of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 52 publications
(71 reference statements)
7
92
0
Order By: Relevance
“…As shown in Figure 3 E left and Figure 3 F, both IL-18R hi and IL-18R lo kidney Trm cells produced similar levels of IFN-γ upon re-stimulation. Consistent with recent findings that non-lymphoid tissue Trm cells are reactivated less efficiently than their lymphoid tissue counterparts ( Low et al., 2020 ), both IL-18R hi and IL-18R lo Trms produced less IFN-γ than splenic memory T cells. Alternatively, this finding may be explained by inefficient access to cognate peptide for Trms in vivo .…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 3 E left and Figure 3 F, both IL-18R hi and IL-18R lo kidney Trm cells produced similar levels of IFN-γ upon re-stimulation. Consistent with recent findings that non-lymphoid tissue Trm cells are reactivated less efficiently than their lymphoid tissue counterparts ( Low et al., 2020 ), both IL-18R hi and IL-18R lo Trms produced less IFN-γ than splenic memory T cells. Alternatively, this finding may be explained by inefficient access to cognate peptide for Trms in vivo .…”
Section: Resultssupporting
confidence: 90%
“…In lung tissue for example, pulmonary monocytes interact with effector T cells to drive T RM cell differentiation following viral infection (Dunbar et al, 2020). It has recently been shown that lung T RM cells can be reactivated by numerous hematopoietic and non-hematopoietic antigen-presenting cells, but the identity of the antigen-presenting cells influenced the functional properties iScience Article of the T RM cells (Low et al, 2020). In the liver, Kupffer cells and stromal cells are the sources of soluble mediators (e.g., IL-6, IL-10, and TGFb) capable of modulating the phenotype of T cells, and the unique signature of such cytokines but also of other factors may further instruct T cells in each tissue type, and this may trigger the phenotypic differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…Research from the Salk Institute has uncovered how memory T cells that are responsible for long-term immunity in the lungs can be reactivated more easily than previously thought. 124 The results reveal a novel tissue-specific paradigm for the reactivation of memory CD8 + T cells which could aid in the development of universal vaccines for both influenza and SARS-CoV-2. In a separate study, in vitro tests have shown that DNA origami particles, which are folded intricately to mimic the size and shape of viruses, provoked a strong immune response from human immune cells.…”
Section: Covid-19 Prevention: Development Of New Vaccinesmentioning
confidence: 94%